IMPLEMENTASI STANDAR NASIONAL PENDIDIKAN PADA STANDAR PENDIDIK DAN TENAGA KEPENDIDIKAN DI SEKOLAH DASAR: IMPLIKASINYA PADA MANAJEMEN SEKOLAH DASAR - Maesaroh, Iis; Jakaria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving the quality of basic education is strongly influenced by the quality of educators and education personnel. The National Education Standards (SNP) have set Educator and Education Personnel Standards as minimum indicators to ensure quality education services. This article aims to examine the implementation of these standards in primary schools and analyze their implications for school management. The method used is a literature review of relevant laws and regulations, books, scientific journals and research reports. The results of the study show that the implementation of the CFS in primary schools faces various challenges such as inequality in teacher competence, limited ongoing training, and the minimal role of education personnel in supporting the learning process. Implications for school management include the need for transformational leadership, strengthening academic supervision and improving human resource planning. Synergy between principals, teachers and other stakeholders is needed for this standard to be implemented effectively and sustainably.